Chapter Punktzeit als (Ver-)Störung Über filmische Narrative absoluter Feindschaft - Koch, Lars (De Gruyter, 2013)
This collected volume aims to generate a concise theoretical presentation of the "perturbation principle" in the humanities and the natural sciences. Incorporating findings from natural scientific research, the contributors attempt to take further steps along the way to a general "theory of perturbation."